Contemporary management of subclavian and axillary artery injuries—A Western Trauma Association multicenter review. Issue 6 (December 2017) - Waller, Christine J.; Cogbill, Thomas H.; Kallies, Kara J.; Ramirez, Luis D.; Cardenas, Justin M.; Todd, S. Rob; Chapman, Kayla J.; Beckman, Marshall A.; Sperry, Jason L.; Anto, Vincent P.; Eriksson, Evert A.; Leon, Stuart M.; et al.
Abstract : BACKGROUND: Subclavian and axillary artery injuries are uncommon. In addition to many open vascular repairs, endovascular techniques are used for definitive repair or vascular control of these anatomically challenging injuries. The aim of this study was to determine the relative roles of endovascular and open techniques in the management of subclavian and axillary artery injuries comparing hospital outcomes, and long-term limb viability. METHODS: A multicenter, retrospective review of patients with subclavian or axillary artery injuries from January 1, 2004, to December 31, 2014, was completed at 11 participating Western Trauma Association institutions. Statistical analysis included χ 2, t -tests, and Cochran-Armitage trend tests. A p value less than 0.05 was significant. RESULTS: Two hundred twenty-three patients were included; mean age was 36 years, 84% were men. An increase in computed tomography angiography and decrease in conventional angiography was observed over time ( p = 0.018). There were 120 subclavian and 119 axillary artery injuries. Procedure type was associated with injury grade ( p < 0.001). Open operations were performed in 135 (61%) patients, including 93% of greater than 50% circumference lacerations and 83% of vessel transections. Endovascular repairs were performed in 38 (17%) patients; most frequently for pseudoaneurysms. Fourteen (6%) patients underwent a hybrid procedure. Use of endovascular versus open procedures did not increase over the duration of the study ( p = 0.248). In-hospital mortality rate was 10%. Graft or stent thrombosis occurred in 7% and graft or stent infection occurred in 3% of patients. Mean follow-up was 1.6 ± 2.4 years (n = 150). Limb salvage was achieved in 216 (97%) patients. CONCLUSION: The management of subclavian and axillary artery injuries still requires a wide variety of open exposures and procedures, especially for the control of active hemorrhage from more than 50% vessel lacerations and transections. Endovascular repairs were used most often for pseudoaneurysms. Low early complication rates and limb salvage rates of 97% were observed after open and endovascular repairs. LEVEL OF EVIDENCE: Prognostic/epidemiologic, level IV. Abstract : Supplemental digital content is available in the text.